Peningkatan Keterampilan Membaca Pemahaman Menggunakan Model Cooperative Integrated Reading and Composition Berbantu Media Word Box di Kelas 3 Sekolah Dasar Negeri 36/VI Rantau Panjang III - Dahlia Dahlia; Aprizan Aprizan; Aldino Aldino (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study was motivated by the low reading comprehension ability of third-grade students at SD Negeri 36/VI Rantau Panjang III. Initial observations showed that many students struggled with recognizing letters, spelling, and understanding the content of texts. The purpose of this study was to describe the process of teaching reading comprehension and to improve student learning outcomes through the implementation of the Cooperative Integrated Reading and Composition (CIRC) model supported by the Word Box media. The research method used was Classroom Action Research (CAR), conducted in two cycles. Data collection techniques included observation, learning outcome tests, and documentation. The results showed an improvement in students’ reading comprehension skills from the first to the second cycle, both in terms of active student participation and the number of students achieving the expected competencies based on the learning objectives. The conclusion of this study confirms that the CIRC model combined with Word Box media is effective in enhancing students' reading comprehension skills. In the future, this model has the potential to be implemented more widely as an active, engaging, and collaborative approach to teaching Indonesian at the elementary school level.